2012
DOI: 10.1111/j.1439-0507.2012.02215.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of distal subungual onychomycosis with a topical preparation of urea, propylene glycol and lactic acid: results of a 24‐week, double‐blind, placebo‐controlled study

Abstract: Onychomycosis is difficult to cure as this requires eradication of the primary infection and protection of new areas of growth from reinfection. A new topical treatment (K101) has been developed. The aim of this study was to assess the efficacy, safety and tolerability of K101 treatment of distal subungual onychomycosis. This was a 24-week (plus 2-week washout), multicentre, randomised, double-blind, placebo-controlled study in 493 patients with distal subungual onychomycosis (K101, n = 346; placebo, n = 147),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 27 publications
1
18
1
Order By: Relevance
“…The proportion of patients who were mycologically cured after 24 weeks of treatment (plus a 2-week washout) was higher for K101 than for a placebo preparation (27.2 vs. 10.4%). In addition, more patients receiving K101 judged that their condition had improved, with statistically significant differences versus placebo from 2 weeks until the end of the study at 26 weeks [17] . In a separate study, nail psoriasis patients treated for 16 weeks with a lotion containing propylene glycol and urea showed significant improvements in nail pitting, subungual keratosis, and onycholysis [18] .…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of patients who were mycologically cured after 24 weeks of treatment (plus a 2-week washout) was higher for K101 than for a placebo preparation (27.2 vs. 10.4%). In addition, more patients receiving K101 judged that their condition had improved, with statistically significant differences versus placebo from 2 weeks until the end of the study at 26 weeks [17] . In a separate study, nail psoriasis patients treated for 16 weeks with a lotion containing propylene glycol and urea showed significant improvements in nail pitting, subungual keratosis, and onycholysis [18] .…”
Section: Introductionmentioning
confidence: 99%
“…Previously, mycological cure after K101 treatment for 6 months was 27.2% (dermatophyte-confirmed onychomycosis with ≤50% of nail involvement), while patient-rated reduction or patient-rated absence of symptoms was reported by 42.9% [12]. The current study included patients with up to 75% of nail involvement; complete and mycological cure of dermatophyte infections after 15 months of K101 solution alone were 33.3 and 48.5%, respectively.…”
Section: Discussionmentioning
confidence: 74%
“…This study clearly documented the efficacy of K101 Nail Solution against these fungi in vitro with very good MCC values. Other studies have shown the clinical efficacy of K101 Nail Solution in the treatment of nails affected by onychomycosis …”
Section: Discussionmentioning
confidence: 99%
“…K101 Nail Solution is a mixture of propylene glycol, lactic acid and urea. The pH is approximately 4 which may contribute to its efficacy, compared with other topical agents . It is well known that a low pH in skin and nails is important for the antimicrobial protection against both pathogenic fungi and bacteria .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation